Responses of yield, root traits and their plasticity to the nitrogen environment in nitrogen-efficient cultivars of drip-irrigated rice - Qingyun Tang; Guodong Wang; Lei Zhao; Zhiwen Song; Yuxiang Li (Journal of Integrative Agriculture, 2025)
The responses of drip-irrigated rice physiological traits to water and fertilizers have been widely studied. However, the responses of yield, root traits and their plasticity to the nitrogen environment in different nitrogen-efficient cultivars are not fully understood. An experiment was conducted from 2020–2022 with a high nitrogen use efficiency (high-NUE) cultivar (T-43) and a low-NUE cultivar (LX-3), and four nitrogen levels (0, 150, 300, and 450 kg ha–1) under drip irrigation in large fields. The aim was to study the relationships between root morphology, conformation, biomass, and endogenous hormone contents, yield and NUE. The results showed three main points: 1) Under the same N application rate, compared with LX-3, the yield, N partial factor productivity (PFP), fine root length density (FRLD), shoot dry weight (SDW), root indole-3-acetic acid (IAA), and root zeatin and zeatin riboside (Z+ZR) of T-43 were significantly greater by 11.4–18.9, 11.3–13.5, 11.6–15.7, 9.9–31.1, 6.1–48.1, and 22.8–73.6%, respectively, while the root–shoot ratio (RSR) and root abscisic acid (ABA) were significantly lower (P<0.05); 2) nitrogen treatment significantly increased the rice root morphological indexes and endogenous hormone contents (P<0.05). Compared to N0, the yield, RLD, surface area density (SAD), root volume density (RVD), and root endogenous hormones (IAA, Z+ZR) were significantly increased in both cultivars under N2 by 61.6–71.6, 64.2–74.0, 69.9–105.6, 6.67–9.91, 54.0–67.8, and 51.4–58.9%, respectively. Compared with N3, the PFP and N agronomic efficiency (NAE) of nitrogen fertilizer under N2 increased by 52.3–62.4 and 39.2–63.0%, respectively; 3) the responses of root trait plasticity to the N environment significantly differed between the cultivars (P<0.05). Compared with LX-3, T-43 showed a longer root length and larger specific surface area, which is a strategy for adapting to changes in the nutrient environment. For the rice cultivar with high-NUE, the RSR was optimized by increasing the FRLD, root distribution in upper soil layers, and root endogenous hormones (IAA, Z+ZR) under suitable nitrogen conditions (N2). An efficient nutrient acquisition strategy can occur through root plasticity, leading to greater yield and NUE.